1998
DOI: 10.1007/s005990050003
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic markers in surgery: a different fibrinolytic activity may be of pathophysiological significance in orthopedic versus abdominal surgery

Abstract: Without prophylaxis, patients subjected to major abdominal surgery have a risk of deep vein thrombosis of approximately 30%, while the rate varies between 40% and 60% in orthopedic surgery. The reasons for this discrepancy are not completely understood. The present study was designed to compare the pre-and postoperative behavior of different coagulation and fibrinolysis parameters in patients undergoing both types of surgery, receiving low molecular weight heparin prophylaxis. Samples were taken before operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…Much less pronounced were the changes during cholecystectomy and thyroid resection ( Table 4). Similar results were reported by Diamantis et al 80 , who examined differences in activation of coagulation and fibrinolytic pathways between open and laparoscopic surgery, and by López and co-workers 77 , who studied postoperative differences between orthopaedic and abdominal surgery. Overall, in these studies surgery led to hypercoagulability, with open surgery leading to a stronger activation of the clotting system in plasma than laparoscopic procedures 77,79,80 .…”
Section: Fibrinolytic and Coagulatory Response To Surgery Measured Insupporting
confidence: 75%
See 2 more Smart Citations
“…Much less pronounced were the changes during cholecystectomy and thyroid resection ( Table 4). Similar results were reported by Diamantis et al 80 , who examined differences in activation of coagulation and fibrinolytic pathways between open and laparoscopic surgery, and by López and co-workers 77 , who studied postoperative differences between orthopaedic and abdominal surgery. Overall, in these studies surgery led to hypercoagulability, with open surgery leading to a stronger activation of the clotting system in plasma than laparoscopic procedures 77,79,80 .…”
Section: Fibrinolytic and Coagulatory Response To Surgery Measured Insupporting
confidence: 75%
“…Many surgeons assume that laparoscopy induces fewer adhesions than laparotomy owing to less peritoneal trauma. Previous studies showed that open surgery led to a significantly greater activation of the clotting system in plasma than laparoscopic procedures 77,78,80 . Adhesion formation, however, has not been evaluated properly as primary endpoint in prospective studies comparing laparoscopy and laparotomy.…”
Section: Factors Influencing Inflammation Coagulation Fibrinolysis mentioning
confidence: 98%
See 1 more Smart Citation
“…This surgery-induced 'shut down' of fibrinolytic activity is thought to be related to a peroperative release of platelet PAI-1 [14], high levels of the pituitary hormone arginine vasopressin [15] and of inflammatory cytokines [16] in response to the surgical stress which induces a release of the endothelial protein PAI-1. A difference in fibrinolytic response according to the type of surgery has been described when comparing orthopaedic and abdominal surgery [17]. In only concerned the intensity of decrease in fibrinolytic activity (which is more pronounced in orthopaedic surgery).…”
Section: Discussionmentioning
confidence: 99%
“…It develops after surgery from activation of the hemostatic system and partial shutdown of the fibrinolytic system, and has been shown to correlate well with the extent of surgical trauma [19,28].…”
Section: Introductionmentioning
confidence: 99%